N-acetylcysteine expresses powerful anti-inflammatory and antioxidant activities resulting in complete improvement of acetic acid-induced colitis in rats - (:unkn) unknown (INFORMA HEALTHCARE, 2013)
High free radical production, low antioxidant capacity and excessive inflammation are well known features in the pathogenesis of inflammatory bowel disease. N-acetylcysteine (NAC) is a powerful antioxidant and a scavenger of hydroxyl radicals. Recently, NAC has also been shown to have anti-inflammatory activities in tissues. Our study objective was to investigate the effects of NAC on tissue inflammatory activities using an ulcerative colitis model induced by acetic acid (AA) in rats. Wistar rats (n = 32) were divided into four groups. AA-induced colitis was performed in two of the groups while the other two groups were injected with saline intrarectally. One of the AA-induced colitis groups and one of the control groups were administered NAC (500 mg/kg/day) intrarectally, and the other control groups were given saline. After 4 days, colonic changes were evaluated biochemically by measuring proinflammatory cytokines [tumor necrosis factor (TNF)-alpha, interleukin (IL)-1 beta and IL-6], myeloperoxidase (MPO), malondialdehyde (MDA), glutathione (GSH) and superoxide dismutase (SOD) levels in tissue homogenates and by histopathological examination. AA caused colonic mucosal injury, whereas NAC administration suppressed these changes in the AA-induced colitis group (p < 0.001). AA-administration resulted in increased TNF-alpha, IL-1 beta, IL-6, MPO and MDA levels, and decreased GSH and SOD levels, whereas NAC reversed these effects (all p < 0.001). In conclusion, the present study proposes that intrarectal NAC therapy has a dual action as an effective anti-inflammatory and an antioxidant, and may be a promising therapeutic option for ulcerative colitis.
Keywords: N-acetylcysteine; ulcerative colitis; inflammatory bowel disease; oxidative stress; tumor necrosis factor; interleukin; cytokine; ULCERATIVE-COLITIS; INFLAMMATION; FIBROSIS; ASSAY